Associação e fatores de risco entre as doença de Alzheimer, doença de Parkinson e periodontite: um estudo caso-controle - Augusto Paixão Morais Mateus (2022)
Recent scientific evidence has demonstrated a possible association between periodontitis (PE) and neurodegenerative diseases (ND). However, further clarification is needed. Therefore, the aim of this case-control study was to evaluate the clinical and epidemiological aspects of the association between PE and ND [which are represented in this study by Alzheimer's Disease (AD) and Parkinson's Disease (PKD)], along with the influence of several risk factors involved in that association. A case-control study was carried out with 223 people, 96 of which with ND (AD: n=43 and PKD: n=53) and 127 controls without ND. Complete periodontal examinations were performed in order to record plaque index (PI), probing depth (PD), clinical attachment level (CAL) and bleeding on probing (BOP), and collection of biological and sociodemographic variables of interest. The association among PE, ND and their risk variables was tested using univariate analysis and multivariate logistic regression. A high prevalence of PE (OR; 95% CI) was observed in the ND, AD and PKD groups, respectively, 67.7% (5.46; 3.0-9.8; p<0.001), 60.4% (3.98; 1.9-8.3; p<0.001) and 73.5% (7.22; 3.5-15.3; p<0.001). In the multivariate logistic regression analysis the ND groups were associated with: PE (4.23; p<0.001), age (2.03; p=0.021, fewer teeth (1.98; p<0.001), use of antidepressants (8.45, p<0.001) and anxiolytics (19.98; p<0.001). A protective effect was observed for the variables: non-use of alcohol (0.21; p<0.001) and schooling of 8 years or more (0.26; p<0.001). This study demonstrated a strong risk association among Alzheimer's, Parkinson's, and periodontitis diseases.